Decreased erythrocyte superoxide dismutase in elderly men with early nuclear cataract - Rose Rose; Erlani Kartadinata (Universa Medicina, 2014)
BACKGROUND Imbalance between oxidative processes and antioxidant defenses has been considered to play a role in cataractogenesis, particularly in diabetes patients. Superoxide dismutase (SOD) is an important precursor for oxidative stress in the human lens, and its activity is mainly dependent on the copper and zinc levels in the body. The aim of this study was to compare erythrocyte SOD, erythrocyte zinc and total serum testosterone levels in male patients with early senile nuclear cataract and evaluate the correlations between the parameters in all subjects. METHODS A community-based study of cross-sectional design was conducted at Cilandak District Primary Health Center where 52 adult and 17 elderly men with early senile nuclear cataract were chosen as the study subjects. Erythrocyte SOD, erythrocyte zinc, serum testosterone, and fasting blood glucose (FBG) levels were measured in all subjects. Nuclear cataract stage was assessed with the Pentacam® instrument (Oculus, Germany). Independent Student t test and Pearson’s correlation were used to analyze the results. RESULTS Erythrocyte SOD level was significantly decreased in elderly men compared to adult men (p=0.014). Erythrocyte zinc, serum testosterone and FBG did not differ significantly in adult and elderly males (at p=0.304; p=0.145;and p=0.376, respectively). Erythrocyte SOD activity was significantly associated with erythrocyte zinc level (r=0.486; p=0.048). CONCLUSIONS Lower erythrocyte SOD activity was found in elderly males than in adult males with early nuclear cataract. There was a relationship between erythrocyte SOD and erythrocyte zinc level in elderly males with early nuclear cataract.